Perbedaan Hasil Belajar Siswa Menggunakan Model Numbered Head Together (NHT) Dikombinasikan Dengan Mind Mapping Dan NHT Tanpa Mind Mapping Pada Materi Ekosistem Di Kelas X SMARK SerdangMurni Lubuk Pakam Tahun Pembelajaran 2014/2015 - Erna Simbolon; Ashar Hasairin (Jurnal Pelita Pendidikan, 2015)
This research was aimed to determine the type of each difference in the model Numbered Head Together combined with Mind Map and without Mind Map against learning result on ecosystem in class X SMA RK Serdang Murni Lubuk Pakam of school year 2014/2015. This research was experimental through implemented different strategy. The population in this research was all students of class X consisting 4 classes, totaling 167 people. While the research sample was taken randomly sampling in class Xa was made as a class which use Mind Mapping with Numbered Head Together model and Xb as class use NHT, with each number of student’s in class are43 people. According to the data analysis of student learning outcomes seen a significant difference in learning outcomes for which the average student learning outcomes are taught using Numbered Head Together combined with Mind Mapping at 82,90 while the average learning outcomes of students who are taught use NHT at 77,44. The difference in student learning outcomes in both classroom study demonstrated through hypothesis testing using t-test with a confidence level, where tcount ttable (3,23 1,67), which means that in this study H0 is rejected at the same time so that it can accept Ha concluded that there are differences in learning outcomes of students who are taught using Numbered Head Together model combined with Mind Map and without Mind Map against learning result about ecosystem in class X SMA RK Serdang Murni Lubuk Pakam of school year 2014/2015.Keywords: learning outcomes, numbered head together, mind mapping